Surface roughness specifications context in costa rican rehabilitation projects - Solís Salas, Verónica (2025)
To guarantee pavement performance in rehabilitation projects with asphalt overlays, the implementation of technical specifications that enables the assessment of its construction quality is necessary. The applicability of the specifications must be validated in terms of achieved values from past projects altogether with international references, where similar specifications have gone into effect, followed up with the validation of the results. In the present project, the applicability of the specifications from the Manual of general specifications for road and bridge constructions in Costa Rica is analyzed with the requirements of bid paper N°2014LN- 000018-0CV00 for nine projects with asphalt overlay interventions in the last two years. From the investigation it can be concluded that the established range of values in the specifications matches the ones in countries like Chile, Colombia, Spain and United States. Additionally, the results showed that, even though said specifications were not valid for the bid paper, acceptable compliance was achieved, which indicates the applicability of the normative in the Costa Rican reality. Finally, as a product of the investigation, improvements for the current specifications were defined, where these can be verified in actual projects.